Performance, genetic and ecological insights for the conservation of the endangered large pink, Dianthus superbus L. (Caryophyllaceae) in semi-natural grassland. Issue 1 (2nd January 2019) - Hardion, Laurent; Pouvreau, Marine; Schwoertzig, Eugénie; Hoff, Michel; Nguefack, Julie; Combroux, Isabelle
ABSTRACT: The traditional management of hay meadows has allowed them to maintain a notable part of biodiversity currently threatened by recent changes in agricultural uses. In the North Eastern region of France, the large pink, Dianthus superbus L. (Caryophyllaceae), mainly grows in hay meadows, and its protected status implies a conservation strategy merging information about its demography, its genetic diversity and its ecology. This study has revealed that the population size of D. superbus is correlated with the trophic status of meadows, with a decrease from mesotrophic to eutrophic meadows. No relation has been established between population size and habitat size, spatial isolation or habitat connectivity. Moreover, AFLPs genetic fingerprints indicated equivalent genetic diversities among meadows, without impact of population size or habitat characteristics. The absence of genetic structure and the lack of population differentiation suggest a large genetic admixture at the regional scale. The most crucial issue for the conservation of D. superbus in the North Eastern region of France seems to be the modification of its habitat due to the eutrophication of hay meadows.